Online Home Pharmacy Care Prototype - Savita, Putri Diana; Miftahuda, Dwiky; Safi'a, Winda Alawiyah; Pribadi, Prasojo; Santoso, Setiyo Budi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This article presents the design of an online pharmacy service application at home. Development of application workflows using software in the draw.io network. The development includes a consultation menu, ordering medication/prescription redemption, camera features to take pictures (prescriptions), payments, and delivery messages.